Aplikasi Persamaan Bessel Orde Nol Pada Persamaan Panas Dua Dimensi - Annisa Eki Mulyati; Sugiyanto Sugiyanto (Program Studi Matematika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2013)
Bessel differential equation is one of the applied equation in physics is about heat transfer. Application of modified Bessel function of order zero on heat transfer process of two-dimensional objects which can be modelled in the form of a two-order partial differential equations as follows, ..... With the obtained solutions of Bessel's differential equation application of circular fin, .... two-dimensional temperature stated on the point ..... against time t